Perlindungan Konsumen atas Metode Penawaran Negative Option di Indonesia - Elizabeth Anastasia; Dwi Sekar Ningrum; William Marthianus; Willis Patrick Onggo (Universitas Medan Area, 2019)
Negative Option Method is a bidding method that requires confirmation from consumers in accepting or rejecting an offer. If the customer doesn’t provide confirmation, the business actor assumes that the consumer agrees and will be charged a fee for the offer given. The Negative Option method originating from the United States has actually developed in Indonesia, especially in the provision of telecommunications services. It is not uncommon for Telecommunications Service Providers in Indonesia to offer a particular feature that requires confirmation of rejection or cancellation from consumers via message, such as